SOCIAL EXCLUSION AND GANGS IN ASYLUM SEEKER AND IMMIGRANT STUDENTS (Third Sector Social Economic Review, 2019)
This study was carried out with the aim of revealing the problem of social exclusion and mobbing which is likely to live or live in asylum seekers and immigrant students and to evaluate the problem within the scope of school social services. For this purpose, Karabük Association for Solidarity with Asylum Seekers and Migrants (ASAM) to take advantage of studying in Turkey in the 7-20 age range, or who has seen a period of 16 students were taken to study sample. Research data were collected by face to face interviews with the students. In the study, social exclusion and mobbing cases of students in schools were analyzed. According to the results obtained from the research, it was determined that asylum seekers and immigrant students were exposed to discriminatory attitudes by their teachers in schools, they were not supported for academic achievement, they were ignored and they were met by their friends with labeling and judgmental attitudes. These results showed that the asylum-seeker immigrant students were absent and to be insensitive to academic achievement. According to the findings, it was observed that the guidance services were insufficient in the schools, the activities were not carried out in the schools, the children were not aware of the guidance services and the psychological counselors in the schools. Awareness should be raised about asylum seekers and immigrant students for the solution of the problems, not only the refugees and immigrants living in the problem, but also the staff, students and parents at the school. Guidance services in schools should be supported by different professions (social workers, psychologists) and school social service units should be established by following the paths for adaptation programs and solving problems.
Keywords: Social exclusion; gangs; refugee student; social cohesion